Numerical calculating linear vibrations of third order systems involving fractional operators - Khang, Nguyen Van; Son, Tran Dinh; Thuy, Bui Thi (Vietnam Journal of Mechanics, 2012)
This paper presents a numerical method for dynamic calculation of third order systems involving fractional operators. Using the Liouville-Rieman's definition of fractional derivatives, a numerical algorithm is developed on base of the well-known Newmark integration method to calculate dynamic response of third order systems. Then, we apply this method to calculate linear vibrations of viscoelastic systems containing fractional derivatives.